Carry trade ETF - Rosenthal, Jean W., (SAGE Knowledge. Cases., 2017)
In 2006 Deutsche Bank (DB) brought a new product to market an exchange traded fund (ETF) based on the carry trade, a strategy of buying and selling currency futures.The Deutsche Bank ETF allowed individual investors to participate in a strategy that previously had been available only through hedge funds or direct purchase of currencies and futures. It was developed at the Deutsche Bank AG New York's Global Currencies & Commodities Group, led by Yale SOM grad Kevin Rich and marketed by PowerShares. The product was launched in September 15, 2006, under the ticker DVB. It traded initially on the American Stock Exchange (AMEX). (As of October 2008 the American Stock Exchange was acquired by NYSE Euronext (NYX) and rebranded as NYSE Alternext).